2017
DOI: 10.12659/msm.901064
|View full text |Cite
|
Sign up to set email alerts
|

Application Value of Mass Spectrometry in the Differentiation of Benign and Malignant Liver Tumors

Abstract: BackgroundDifferentiation of malignant from benign liver tumors remains a challenging problem. In recent years, mass spectrometry (MS) technique has emerged as a promising strategy to diagnose a wide range of malignant tumors. The purpose of this study was to establish classification models to distinguish benign and malignant liver tumors and identify the liver cancer-specific peptides by mass spectrometry.Material/MethodsIn our study, serum samples from 43 patients with malignant liver tumors and 52 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…It has oncogenic effects by binding to vascular endothelial growth factor, promoting endothelial cell proliferation, and interacting with stromal proteins by using integrins as a scaffold for cell migration. 17 In previous studies, high levels of fibrinogen α chain fragments were detected in cholangiocarcinoma, 18 hepatocellular carcinoma, 19 and gastric carcinoma. 20 Klupczynska et al 21…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…It has oncogenic effects by binding to vascular endothelial growth factor, promoting endothelial cell proliferation, and interacting with stromal proteins by using integrins as a scaffold for cell migration. 17 In previous studies, high levels of fibrinogen α chain fragments were detected in cholangiocarcinoma, 18 hepatocellular carcinoma, 19 and gastric carcinoma. 20 Klupczynska et al 21…”
Section: Discussionmentioning
confidence: 91%
“…It was indicated that tumor cells can promote blood coagulation by interacting with endothelial cells and platelets, and releasing active substances to activate platelets, resulting in increased fibrinogen levels in the blood of cancer patients. In previous studies, high levels of fibrinogen α chain fragments were detected in cholangiocarcinoma, 18 hepatocellular carcinoma, 19 and gastric carcinoma 20 . Klupczynska et al 21 combined ZipTip technology with MALDI‐TOF‐MS for the first time to study the serum proteome of patients with NSCLC and healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Further reports described increased expression of fibrinogen in a large variety of tumors (57)(58)(59) and correlation of high fibrinogen plasma levels with cancer risk, worse disease-free and poor overall survival (59)(60)(61). Peptides derived from the C-terminus of fibrinogen a (62-64), including a peptide identical to Fa27 (65), were also identified during clinical association studies in search of serumderived tumor biomarkers. Notably, one study focusing on acute myeloid leukemia (AML) showed that a 38 amino acid long Cterminal fragment of fibrinogen a encompassing Fa27 was found to be reduced in sera from newly diagnosed, refractory and relapsed cases and associated with improved overall survival of patients, which was the opposite of what was observed for the fibrinogen a level (62).…”
Section: Discussionmentioning
confidence: 99%
“…MALDI-TOF MS is a valuable tool for the profiling of biological samples with relatively low abundance that is fast, highly sensitive, and has a high throughput [20]. In addition, the use of MALDI-TOF MS combined with magnetic beads is a new method that has been used to identify cancer and other diseases [21][22][23][24][25]. This method is also suitable for detection of serum protein biomarkers in liver transplant patients.…”
Section: Discussionmentioning
confidence: 99%